Perancangan dan Simulasi Computational Fluid Dynamics (CFD) pada Tabung Mesin Rotary Dryer untuk Pengeringan Batu Kapur dalam Industri Semen - Mulyaningsih, Nani; Prasetyo, Arief; Taufik, Ikhwan (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
The cement industry is one of the most important industries to fulfill the needs of infrastructure, construction, and development. The rotary dryer, as a commonly used drying equipment in the cement manufacturing industry, works with the principle of flowing heat directly into a rotating tube containing raw materials to be dried. The research was conducted by designing a rotary dryer with dimensions of 3100 mm long, 1000 mm wide, 620 mm high, and 750 mm diameter tube and 2400 mm long using SolidWorks 2022 software and simulating the machine frame using Ansys 2023 software. This machine uses a 20 HP electric motor to drive the tube during the drying process with a tube capacity of 450 kg/hour and a rotating speed of 15 rpm. The frame material uses AISI 1020 steel. Based on the CFD simulation results on the rotary dryer machine tube, the best heat distribution with drying efficiency seen from the heat distribution is 74%.